Piperazine skeleton in the structural modification of natural products: a review - Run-Hui Zhang; Hong-Yan Guo; Hao Deng; Jinzi Li; Zhe-Shan Quan (Taylor & Francis Group, 2021)
Piperazine moiety is a cyclic molecule containing two nitrogen atoms in positions 1 and 4, as well as four carbon atoms. Piperazine is one of the most sought heterocyclics for the development of new drug candidates with a wide range of applications. Over 100 molecules with a broad range of bioactivities, including antitumor, antibacterial, anti-inflammatory, antioxidant, and other activities, were reviewed. This article reviewed investigations regarding piperazine groups for the modification of natural product derivatives in the last decade, highlighting parameters that affect their biological activity.